Factores de riesgo asociados a retinopatía de la prematuridad en el Hospital Víctor Lazarte Echegaray enero 2014 - diciembre 2016 - Silva Boyd, Karla Jeniffer (2019)
Objective: To determine if the factors under study: gestational age, very low birth weight, oxygen therapy, anemia, malnutrition and neonatal sepsis are associated with retinopathy of prematurity. Materials and methods: Study cases and controls, the group of cases will be formed by 58 patients and the control group 116 patients; We will review clinical histories of premature newborns in the Neonatology service of Víctor Lazarte Echegaray Hospital, in the period January 2014- December 2016. To analyze the data, double-frequency frequency distribution tables will be constructed with their absolute and relative values, determining the association between independent variables (presumed risk factors) with retinopathy of prematurity (dependent variable); the Chi square test (X2) will be used, in the case of nominal variables and the student's t test for quantitative variables; the associations were considered significant if the possibility of being wrong was less than 5% (p <0.05). To determine which variables were risk factors, the odds ratio and 95% confidence interval will be calculated. Key words: Retinopathy of prematurity and risk factors.